Pengaruh Pemberian Pupuk Bokashi Terhadap Pertumbuhan dan Produksi Tanaman Seledri (Apium Graveolens L.) - Hafizah Asby; Husnarika Febriani; Efrida Pima Sari Tambunan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2019)
wet weight, but did not have a significant effect on the number of celery stems (Apium and Celery (Apium graveolens L.) is a vegetable plant that has very bright prospects. Every year the population that continues to increase causes the need for vegetables to also increase. So to meet the needs of consumers celery production needs to be increased. Therefore, it is necessary to look for alternative efforts to increase the yield of celery cultivation, one of which is the application of Bokashi fertilizer. Bokashi is the result of fermentation of organic ingredients with EM4 technology. The purpose of this study was to determine the effect of giving Bokashi on the growth and yield of celery (Apium graveolens L.) and to determine at what dose the application of Bokashi fertilizer on growth and production of celery plants (Apium graveolens L.). The research was conducted at Jalan Sempurna Pasar 7 Termbung and the wet weight of celery was carried out at the Biology laboratory, Faculty of Science and Technology, State Islamic University of North Sumatra, Medan in July 2019 - November 2020. The data obtained were tabulated and analyzed using the One Way Analysis of Variance test. (ANOVA) at the real level (significant) used, namely Î± = 0.05 and continued with the Duncan's Multiple Range Test (DMRT) to see the significant results between treatments. Data analysis was using the software statistical Product and Service Solutions (SPSS) version 23. The results showed that bokashi fertilizer had a significant effect on plant height and production of celery (Apium graveolens L.) is the D4 treatment with a dose of 40 grams. graveolens L. ). 5.1.2 The optimum dose of bokashi fertilizer which has a significant effect on the growth